The Investigations of Gold Tissues Surface from the Сathedral of Assumption (Kyiv) Sarcophagus - A. V. Zazhigalov; S. A. Balakin; I. V. Bacherikova; V. O. Zazhigalov (Хімія, фізика та технологія поверхні, 2010)
The objects of the cultural heritage discovered by archaeologists on the area of ancient Kyiv (Old Russia) were examined by non-destructive techniques such as SEM with EDXRS, XPS and AFM. The topographical examination shows that the fragments of gold tissues (XI–XVI AD) content two kinds of materials: golden spiral threads and light colour flakes. In the composition of the threads, Au is the basic element but the flakes contain C, O, Mg, Al, Si, P, S, Ag, Ca, and Fe. The origin of these flakes today is unknown (the traces of cloth or varnishes possible). The presence of Rb in golden artefacts testifies the existence of own gold output and technology on the area of ancient Kyiv. The absence of Cu, which presents in oldest gold tissue, in the samples manufactured in XV–XVI AD can be connected with an improvement of melting technology. The difference in the composition in the golden threads for all samples examined shows them to be manufactured in various regions of Old Russia.